2022
DOI: 10.1186/s12989-022-00482-x
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor activation-mediated vascular toxicity of ambient fine particulate matter: contribution of polycyclic aromatic hydrocarbons and osteopontin as a biomarker

Abstract: Background Exposure to ambient fine particulate matter (PM2.5) is associated with vascular diseases. Polycyclic aromatic hydrocarbons (PAHs) in PM2.5 are highly hazardous; however, the contribution of PM2.5-bound PAHs to PM2.5-associated vascular diseases remains unclear. The ToxCast high-throughput in vitro screening database indicates that some PM2.5-bound PAHs activate the aryl hydrocarbon receptor (AhR). The present study investigated whether the AhR pathway is involved in the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Studies have shown that the activation of NF-κB and AP-1 signaling pathways is directly involved in the regulation of CYP1A1 by heavy metals. Furthermore, nicotine stimulates CYP1A1 expression through transcription factor, activator protein 1, NF-κB, and aromatic hydrocarbon receptor signaling pathways [26]. In this study, transcriptional analysis revealed significant changes in CYP1A1 after THC treatment in breast cancer cells.…”
Section: Discussionmentioning
confidence: 48%
“…Studies have shown that the activation of NF-κB and AP-1 signaling pathways is directly involved in the regulation of CYP1A1 by heavy metals. Furthermore, nicotine stimulates CYP1A1 expression through transcription factor, activator protein 1, NF-κB, and aromatic hydrocarbon receptor signaling pathways [26]. In this study, transcriptional analysis revealed significant changes in CYP1A1 after THC treatment in breast cancer cells.…”
Section: Discussionmentioning
confidence: 48%
“…yezoensis extract showed no cytotoxicity at any of the concentrations tested ( Figure 1 a). UPM was reported to increase intracellular ROS levels by activating XRE promoter activity [ 24 ]. Therefore, we analyzed XRE promoter activity in cells treated with UPM and with or without P .…”
Section: Resultsmentioning
confidence: 99%
“…BaP is a well-known highly toxic and carcinogenic compound. Recent studies have also reported that Bkf also is the most important contributor to the aryl hydrocarbon receptor activation which participates in the mechanism of PM 2.5 -induced cardiovascular disease, followed by Bbf and Dah (Ho et al 2022 ; Ma et al 2022 ). Bkf was found to adversely affect cell viability and necrosis in the placental cell line, indicating potential reproductive toxicity (Jo et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%